THE INTERPRETATION OF THE CIVIL CODE OF SAINT LUCIA - Floissac, V. (Revue générale de droit, 1983)
The author makes a presentation of the sources of the St. Lucia Civil Code. He then studies some mainly selected rules of interpretation taken from the Privy Council’s decisions in cases where this Court has had to interprete Statute Law or a Code, like the Québec one. The author mentions also the difficulties of interpretation created by the introduction of English Law in the St. Lucia Code.